Biphasic Double-Network Hydrogel With Compartmentalized Loading of Bioactive Glass for Osteochondral Defect Repair - Liu, Bingchuan; Zhao, Yanran; Zhu, Tengjiao; Gao, Shan; Ye, Kaifeng; Zhou, Fang; Qiu, Dong; Wang, Xing; Tian, Yun; Qu, Xiaozhong (Frontiers in Bioengineering and Biotechnology, 2020)
Periarticular injury usually causes the defects of superficial cartilage and the underlying subchondral bone. Although some efficacious outcomes have been achieved by the existing therapeutic methods both in clinics and research, like symptomatic treatment, microfracture surgery, and tissue engineering technology, they still present specific disadvantages and complications. To improve this situation, we designed a biphasic (bi-) scaffold aiming to repair the structure of cartilage and subchondral bone synchronously. The scaffold consisted of a superior double-network (DN) hydrogel layer and a lower bioactive glass (BG) reinforced hydrogel layer, and the DN hydrogel included glycol chitosan (GC) and dibenzaldhyde functionalized poly(ethylene oxide) network, and sodium alginate (Alg) and calcium chloride (CaCl2) network. To investigate its effectiveness, we applied this biphasic scaffold to repair osteochondral full-thickness defects in rabbit models. We set up six observation groups in total, including Untreated group, Microfracture group, BG only group, DN gel group, bi-DN gel group, and bi-DN/TGF-β gel group. With a follow-up period of 24 weeks, we evaluated the treatment effects by gross observation, micro-CT scan and histological staining. Besides, we further fulfilled the quantitative analysis of the data from ICRS score, O’Driscoll score and micro-CT parameters. The results revealed that neat GC/Alg DN hydrogel scaffold was only conductive to promoting cartilage regeneration and neat BG scaffold merely showed the excellent ability to reconstruct subchondral bone. While the biphasic scaffold performed better in repairing osteochondral defect synchronously, exhibiting more well-integrated cartilage-like tissue with positive staining of toluidine blue and col II immunohistochemistry, and more dense trabecular bone connecting closely with the surrounding host bone. Therefore, this method possessed the clinical application potential in treating articular injury, osteochondral degeneration, osteochondral necrosis, and sclerosis.